The Metabolomic study of Calotropis procera Ait. from Burkina Faso, based on chemical functional groups profiling using FTIR - LAGNIKA, LATIFOU (My University, 2020)
Background: C. procera is an important wild medicinal plant used in different area of Burkina Faso for the neuropsychiatric disorders treatment. It was reported to possess many pharmacological properties because of its phytochemical diversity. This study was carried out to identify possible specific chemical characteristics form C. procera leaves and root-bark samples, harvested in two regions of Burkina Faso, for a better selective use of specimens in traditional medicine. Methods: Plant materials (leaves and root-bark) were collected from five sites in each region. Samples powders and extracts were mixed with potassium bromide for the Fourier Transform Infrared Spectroscopy (FTIR) analysis. A multivariate data analysis was performed to highlight differences in the FTIR spectral profile of samples. Therefore, phytochemical contents such as phenolics, flavonoids and terpenoids were evaluated with aqueous and methanolic extracts, using UV/visible light spectrophotometer method. Results: Results of principal component analysis (PCA) showed a significant difference between leaves and root-bark spectral profile, independently to the region of collection. These profiles possess characteristic signals which could be exploited as biomarkers for plant organ discrimination. The phytochemical contents evaluation showed that C. procera leaves contain more significant phenolics, and root-bark possess more terpenoid compounds. This study of C. procera Ait. based on FTIR spectral characteristic and phytochemical content, suggest that terpenoids, notably cardenolide-type could be a good biomarkers for C. procera samples characterization and to explain root-bark therapeutic potential.
Keywords: Burkina Faso; Calotropis procera; FTIR profile; neuropsychiatric; phytochemical